The Impact of Change Management and Work Culture on the Performance of Higher Education Employees - Tedi Priatna (UIN Sunan Gunung Djati, 2023)
This study investigates the impact of change management and work culture on the performance of employees at UIN Sunan Gunung Djati Bandung. It employs an explanatory survey research design with 260 employees selected through simple random sampling. SPSS was utilized for data analysis. The findings indicate that change management significantly influences employee performance during the COVID-19 pandemic, as evidenced by the ttable > tcount (5.604 > 1.969). Work culture also partially impacts employee performance, with ttable > tcount (5.048 > 1.969). The simultaneous effect of change management and work culture is found to strongly affect employee performance (16.667 > 3.030). The study highlights the importance of effective change management and positive work culture in enhancing employee performance. The results could assist policymakers in developing organizational policies that focus on effective change management and work culture to improve employee performance.